Chipless RFID multisensory tags—trends, strengths, challenges, and prospects: a review - Hossain, A. K. M. Zakir; Azam, S. M. Kayser; Ibrahimy, Muhammad Ibn; Uddin, Jasim; Hasan, Mohammad Kamrul; Karmokar, Debabrata Kumar; Zakaria, Zahriladha; Islam, Md. Shazzadul; Al-Gburi, Ahmed Jamal Abdullah (IEEE, 2026)
The concept of chipless radio frequency identification (CRFID) multiparameter tag sensors is fairly new and nowadays has gained importance among researchers for their ability to identify objects and sense multiple parameters at once without requiring integrated chips (ICs), onboard power sources, and active components. This article presents a comprehensive review of such tag sensors, emphasizing its current stage of development, performance comparisons, and existing research gaps. This study provides a detailed classification of resonator structures, identification (ID) and sensing mechanisms, sensing functions and factors, and smart/sensitive materials (SMs), establishing a new unified taxonomy. Furthermore, it provides details on the sensing mechanism and physics behind it, maps resonator types to their design principles with their sensing functions.